A conversation with Jamie Butler. - Stanik, John (New York ACM, 2007)
Rootkitting out all evil
Keywords: Computing Milieux; Management of computing and information systems; Security and protection; General Literature; Miscellaneous; Legal aspects of computing; Legal aspects; Security